Management Practices and Their Engagement Implications: Towards the Learning Community - Miyagui Miyagui, Mónica Mayumi (2024)
Management practices are being implemented in educational institutions within the framework of distributed leadership management for the transformation of the school T hus, the objective of this article is to describe the relationships identified between the variables of the participation of teachers in collegiate meetings and teacher commitment within the framework of the school management practices in which they participate. The sample was made up of 178 teachers from public educational institutions at the primary and secondary education level, from the UGEL Ilo unit, Moquegua. The research was basic, with a quantitative and correlational approach. Two surveys were self administered by participants in Google Forms format. For data processing, the data have been organized in cross tables for the two study variables it has also been deemed convenientto work with the first variable and the dimensions of teacher strengthening and teacher identity as dimensions of the second variable in order to enable a better analysis. Data processing also involved the calculation of the Rho Spearman compensation coefficient, which allowed trends to be confirmed and the results of both procedures to be interpreted. The research results have allowed us to analyze the positive correlations between collegiate meeting and teaching commitment collegiate meeting and teacher strengthening , and c olleg iat e m eeting and t eacher identity.